3D nonlinear constitutive modeling for dynamic analysis of reinforced concrete structural members - Mourlas, Christos; Markou, George; Papadrakakis, Manolis (My University, 2017)
Many constitutive models have been proposed in order to capture the realistic behavior of reinforced concrete structures under static loading conditions. Few of these numerical models manage to extend to dynamic problems. This is due to the fact that these models present increased computational demand and inability to simulate realistically the different types of mechanical behavior of reinforced concrete members. The purpose of this paper is to propose a computationally efficient constitutive method in order to simulate accurately the behavior of a wide range of reinforced concrete structural members under dynamic loading conditions. The proposed material model is based on the Markou and Papadrakakis [1] model which was an extension of the Kotsovos and Pavlovic [2] work. A solution strategy which describes the behavior of concrete during the dynamic loading is presented. The proposed algorithm describes the cyclic behavior of concrete which is dominated by the development of microcracking, macrocracking and brittle failure. It uses the implicit integration method of Newmark in order to solve the equation of motion. The concrete domain is simulated by 8- and 20-noded hexahedral elements, which treat cracking with the smeared crack approach. The steel reinforcement is embedded inside the hexahedral meshing and modeled by truss and beam elements. Accurate nonlinear dynamic analysis of reinforced concrete structures is very helpful in estimating the behavior of a concrete structures during an earthquake. Many concrete buildings have been designed according to the old seismic codes. Thus, an accurate and realistic modeling to assess their strength and their ability to carry the expected seismic forces is very important. The validity of the proposed method is demonstrated by comparing the numerical response with the corresponding experimental results of reinforced concrete members.
Keywords: Nonlinear dynamic analysis; Reinforced concrete; Finite element method; 3D detailed modeling; Smeared crack